Ethical Resolution of Customary Land Disputes Through Harmonizing Tradition and Law - Sulaiman Sulaiman; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2024)
This research examines the customary land disputes between the Tiwu Kondo sub-district government and the Ndoko tribe in East Manggarai, NTT Province. It aims to identify the resolution efforts involving mediation and deliberation with traditional and religious leaders, emphasizing ethical values, local customs, and applicable laws. Using a juridical-empirical approach, data were collected through literature studies, observations, and interviews. Findings reveal that integrating traditional customs and modern legal frameworks, guided by UUPA No.5/1960 and PERDA Manggarai No.1/2018, can effectively resolve disputes, offering a model for fair and sustainable outcomes. Highlights: Integrating Traditions and Laws: Combining customs with modern legal frameworks. Mediation and Deliberation: Involving traditional and religious leaders. Fair and Sustainable Outcomes: Emphasizing ethical values and local norms. Keywords: Land disputes, Customary land, Mediation, Traditional customs, Legal frameworks